THE EFFECTIVENESS OF LOCAL WISDOM-BASED TEACHING MODULES ASSISTED BY HEYZINE FLIPBOOK TO IMPROVE STUDENTS' NUMERACY - Hajriyanto, Muhammad Haris (Prima: Jurnal Pendidikan Matematika, 2025)
This study aims to assess the effectiveness of the results of the development of teaching modules based on local wisdom assisted by heyzine flipbook to improve students' numeracy. This research has novelty in the teaching module development approach, namely by integrating local wisdom and the use of heyzine flipbook through the Luther-Sutopo development model (concept, design, material collecting, assembly, testing, distribution). The approach of local wisdom into learning has an important role in preserving culture and increasing the relevance of teaching materials for students. The research method used was quantitative, with a one group pretest-posttest design. This study involved 23 students of class VII B at SMP Negeri 3 Kalipucang, Pangandaran Regency. Through the pretest and posttest, the study successfully identified significant improvement in learners' numeracy. The average student score increased from 44.28 to 70.85. The average N-Gain value of 0.50 (50%) indicates the achievement of moderate improvement. In addition, statistical analysis using paired sample t-test with a p-value of 0.000 and an effect size of 2.37 proved that the process-differentiated teaching module had a huge impact on improving students' numeracy. The use of this module is effective because it not only improves learning outcomes, but also encourages students to be more familiar with local wisdom in Pangandaran Regency. Thus, this teaching module can be adopted by other educators as one of the tools to support more meaningful learning in improving students' numeracy